Enhancing Elementary Students’ Conceptual Understanding and Interest in Numbers Through Role Play and Menu-Based Mathematics Activities - Ana Ika Ariyani; Havifah Cahyo; Ana Fitrotun Nisa; Berliana Henu Cahyani (STAI Hubbulwathan Duri, 2025)
Mathematics is often perceived as a challenging and abstract subject, leading to low student engagement and understanding. To address this, innovative instructional strategies are needed. This study investigates the effectiveness of the mathematics menu and role-play method in enhancing fourth-grade students’ interest and conceptual understanding of number concepts. A quasi-experimental design was used, involving two groups: an experimental group taught using the mathematics menu and role-play method, and a control group taught using conventional methods. Participants were not randomly assigned. Pre-tests and post-tests were administered to both groups to measure outcomes in the affective (interest) and cognitive (understanding) domains. Multiple-choice assessments served as the primary data collection tools. Data analysis showed that students in the experimental group demonstrated significant improvement in both interest and understanding compared to the control group. The post-test scores of the experimental group were consistently higher across both domains, indicating the positive impact of the intervention. The findings suggest that incorporating the mathematics menu and role-play into instruction effectively fosters student motivation and engagement (affective domain), while also promoting deeper conceptual understanding (cognitive domain). The interactive nature of role-play activities and contextualized learning through the menu approach allowed students to connect abstract concepts to real-life scenarios, making learning more meaningful and enjoyable. This study supports the use of role-play and mathematics menus as effective, student-centered teaching strategies for elementary mathematics, particularly for improving interest and comprehension in number concepts.